ҚАРАҚАЛПАҚ ХАЛҚЫ ТАРИЙХЫН ҮЙРЕНИӮДЕ КӨРКЕМ ӘДЕБИЯТЛАРДЫҢ ОРНЫ - Тлеумуратова, Н.М. (FAN va JAMIYAT, 2021)
The article discusses the role of fiction in the study of the history of the Karakalpak people and the importance of working with works of art and historical sources, as well as the importance of teachers in the study of students both historical and fiction literature of any period in teaching history.